Print-Based Media in Methodology Course of Classroom Action Research - Jalaludin, Jalaludin; Novita, Mona; Asvio, Nova (Journal of Social Work and Science Education, 2021)
Research with the Research and Development (R&D) Method was carried out to produce products in the form of printed learning textbooks as a complement to printed materials in the methodology course of Class Action Research (CAR) at the State Islamic University (UIN) Sulthan Thaha Saifuddin Jambi. This study was divided into three stages: 1) defining; 2) planning and development; and 3) dissemination. The research data were analyzed using domain analysis techniques with critical and reflective principles. Findings printed media for learning textbooks for the CAR methodology course have been developed based on a process approach. The book consists of eleven chapters, covering: 1) recall of CAR concepts; 2) research techniques and CAR data collection instruments; 3) observation sheet; 4) interview sheet; 5) test sheet; 6) questionnaire sheet; 7) documentation in CAR; 8) analysis techniques in CAR; 9) dissemination of CAR reports; 10) write articles from the results of the CAR; and 11) writing a book based on the results of the CAR. The purpose of learning with print media is to help students learn the CAR methodology easily and make learning interesting and fun and enable them to study independently. The developed learning print media is claimed to be suitable for use through a feasibility test carried out by material and media experts to practice making CAR proposals or reports to publishing articles and books with ISBN from the CAR results.